Potential Drug Interactions of Antidiabetic Agents in Geriatric Patients with Type 2 Diabetes Mellitus at the Inpatient Unit of a Hospital in Bandung City - Pasha, ED. Yunisa Mega; Az-Zahro, Lutfiani; Saidah, Siti; Fatin, Mia Nisrina Anbar (Sciences of Pharmacy, 2026)
Type 2 diabetes mellitus is a metabolic disease that commonly occurs in geriatric patients and is generally accompanied by comorbidities. This condition can increase medication use and potentially lead to drug interactions that may affect therapeutic effectiveness and cause adverse effects. This study aimed to identify potential antidiabetic drug interactions and analyze the association between length of hospitalization, number of medications used, and potential drug interactions. This was an analytical observational study with a cross-sectional approach and retrospective data collection using a total sampling technique on 41 medical records of geriatric patients with type 2 diabetes mellitus in the inpatient unit from January to December 2024. Potential drug interactions were identified using Medscape and Drugs.com. with severity levels classified as minor, moderate, and major. The results showed 95 potential antidiabetic drug interactions. Moderate interactions were the most common category, accounting for 88 cases (92.6%), while pharmacodynamic interactions were the most dominant mechanism, with 84 cases (88.4%). Of the 41 patients, 73.2% experienced potential drug interactions. Bivariate analysis using Fisher’s exact test showed a significant association between length of hospitalization, number of medications used, and potential drug interactions (p<0.05). Potential antidiabetic drug interactions in geriatric patients with type 2 diabetes mellitus may be considered in monitoring medication use, especially in patients with polypharmacy and longer hospital stays. However, this study only evaluated potential drug interactions based on a drug interaction database therefore, further studies are needed to assess the clinical manifestations of drug interactions.